Dos miradas a los sectores populares: fotografiando el ritual y la política en México, 1870-1919 - Marino, Daniela (El Colegio de México, A.C., 1998)
This work is divided into two sections, each one consisting of a different methodological approach to the historical analysis of the portrayal of low classes. The two approaches differ in that wheras the first one analyzes how photography was incorporated into a ritual deeply rooted in popular Catholicism -the vigil of children or angelitos ("little angels")-, the second one deals with a completely alien, and therefore stigmatizing, vision of the subordinate group's political world, which in this particular case is zapatismo as an armed opposition to the dominating system.In any case, I find it useful to confront the different perspectives, which  eventually  converge in a semantic image analysis, completely integrated into a social historical  analysis.